2000
DOI: 10.1136/oem.57.9.605
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of lymphohaematopoietic malignancies in a petrochemical industry cohort: 1983–94 follow up

Abstract: Objectives-In response to a previous finding of increased mortality from lymphohaematopoietic (LH) malignancies, this study examines incidence of LH malignancy in a petrochemical industry cohort. Emphasis is on chronic lymphocytic leukaemia (CLL) and on comparisons by period of first employment. Conclusion-These findings do not suggest a continuing excess of CLL but do suggest a small increase in incidence of overall LH malignancy for workers first employed before 1950. This may reflect associations with earli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 21 publications
0
16
0
1
Order By: Relevance
“…A caseÀcontrol study of 98 cases found a positive association between organic solvent exposure and AML [37], and a mortality study of professional chemists observed a significant excess of deaths from this cause [38]. Only one study, however, considered solvents independently of benzene exposure ( Exposure to other aromatic hydrocarbons in petrochemical plants [29,52] or in occupations such as painting, printing or aircraft manufacture [53À57] has been suspected of inducing MM, but a meta-analysis of 22 cohorts did not support this association (Table 10) [58].…”
Section: Suspected Occupational Causesmentioning
confidence: 99%
“…A caseÀcontrol study of 98 cases found a positive association between organic solvent exposure and AML [37], and a mortality study of professional chemists observed a significant excess of deaths from this cause [38]. Only one study, however, considered solvents independently of benzene exposure ( Exposure to other aromatic hydrocarbons in petrochemical plants [29,52] or in occupations such as painting, printing or aircraft manufacture [53À57] has been suspected of inducing MM, but a meta-analysis of 22 cohorts did not support this association (Table 10) [58].…”
Section: Suspected Occupational Causesmentioning
confidence: 99%
“…Relative risks have been near unity in petroleum worker cohort studies in California, 177,178 Texas, [179][180][181] Louisiana, 182,183 US, [184][185][186] Canada 187,188 and Australia. 189 Inconsistent nonsignificant associations were found in an updated (1970-1997) mortality cohort study of 2 refinery/petrochemical plants (SMR for Baton Rouge facility 5 1.47, 95% CI: 0.98-2.11; SMR for Baytown facility 5 0.84, 95% CI: 0.47-1.39).…”
Section: Occupational and Environmental Chemical Exposurementioning
confidence: 99%
“…A similar observation has been reported in two other studies. Workers first employed before 1950 by chemical industries had a predominantly increased risk of lymphohematopoietic malignancies associated with exposure to petroleum solvents [23,24]. This may be attributable to longer duration of exposure to some extent, but more importantly it has been well documented that organic solvent exposures have substantially decreased over time in the work environment because of changes in materials used, improved industrial hygiene measures and regulatory action.…”
Section: Discussionmentioning
confidence: 95%